2015
DOI: 10.1074/jbc.m115.645333
|View full text |Cite
|
Sign up to set email alerts
|

DDIT3 and KAT2A Proteins Regulate TNFRSF10A and TNFRSF10B Expression in Endoplasmic Reticulum Stress-mediated Apoptosis in Human Lung Cancer Cells

Abstract: Background:The mechanisms of transcriptional regulation of TNFRSF10A and TNFRSF10B are not well described. Results: DDIT3 and KAT2A cooperatively up-regulated TNFRSF10A and TNFRSF10B. Conclusion: DDIT3 and KAT2A promote the transcription of TNFRSF10A and TNFRSF10B via the AP-1 and DDIT3 binding sites, respectively. Significance: Our findings offer new insights on the mechanisms of ER stress-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 49 publications
(69 reference statements)
1
86
0
Order By: Relevance
“…If the ER stress is resolved then the DR5 transcripts return to basal levels. Intriguingly, authors described that under persistent ER stress conditions DR5 accumulated in the ER or at the Golgi apparatus depending on the cell type, resulting on DR5 activation independently of TRAIL.Activation of the death receptor TRAIL-R1/DR4 has also been associated to ER stress [62]. It was shown that CHOP interacts with the phosphorylated form of the transcription factor JUN in a complex that binds to the AP-1 binding site within the DR4 promoter region.…”
mentioning
confidence: 99%
“…If the ER stress is resolved then the DR5 transcripts return to basal levels. Intriguingly, authors described that under persistent ER stress conditions DR5 accumulated in the ER or at the Golgi apparatus depending on the cell type, resulting on DR5 activation independently of TRAIL.Activation of the death receptor TRAIL-R1/DR4 has also been associated to ER stress [62]. It was shown that CHOP interacts with the phosphorylated form of the transcription factor JUN in a complex that binds to the AP-1 binding site within the DR4 promoter region.…”
mentioning
confidence: 99%
“…A B С tion IRE1 signaling causes down-regulation of this gene expression, because it was recently shown that DDIT3 and KAT2A proteins regulate TNFRSF10B expression in endoplasmic reticulum stress-mediated apoptosis in human lung cancer cells [20]. However, glucose deprivation has an opposite effect on this gene expression.…”
Section: Fig 3 Effect Of Glucose Deprivation Condition On the Exprementioning
confidence: 99%
“…Conversely the decoy receptors TRAILR3 and TRAILR4, which lack the pro-apoptotic death domain, function to dampen the apoptotic response by competing for TRAIL ligand. TRAILR4 does not induce apoptosis, and has been shown to play an inhibitory role in TRAIL-induced cell apoptosis [20,21,24].…”
mentioning
confidence: 99%
See 2 more Smart Citations